Parâmetros clínicos e bioquímicos salivares após dois protocolos preemptivos da dexametasona na remoção dos terceiros molares em mulheres - Costa, Monique Gonçalves da [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Preemptive therapy improves the patient's quality of life after removal of third molars, however there is no consensus on the most efficient preemptive protocol. The objective was to compare two preemptive protocols of dexamethasone (DEXA) with respect to clinical parameters (edema, trismus and pain), salivary flow (FS) and salivary biochemical parameters: pH, buffering capacity (CT), total protein (PT), phosphatase total alkaline (FAL), total acid phosphatase (FAT), lactate dehydrogenase (LDH), calcium (Ca) and phosphorus (P). This randomized, double-blind, split-mouth clinical study was carried out with eight women, with a mean age of 20.89 years, without local and systemic health problems, who required bilateral upper and lower third molar extractions. Each patient had bilateral surgical removals in two parts, with an interval of 20 days between preparations. In each procedure, a preemptive protocol was used randomly: preoperative oral DEXA at the usual dose, 8 mg, 1 hour before surgery (control group) and the usual fractional dose, 4 mg, 8 and 1 hour before surgery (group experimental) All volunteers signed an informed consent form (CAAE 44625815.8.0000.5420). Clinical parameters were measured in the immediate preoperative period and in the 2 and 7 day postoperative period. In the same periods, the total unstimulated saliva was collected by the sputum method between 2:00 pm to 4:00 pm. After processing, the aliquots of the supernatant were stored at -80 ° C until their analysis by spectrophotometric methods. Preemptive protocols were compared with each other using Student's t test (p < 0,05). To compare the results before surgery and in the postoperative period of each preemptive protocol, an ANOVA statistical analysis was used, followed by the Tukey test (parametric data) and the Kruskal Wallis test followed by Dunn's post hoc multiple comparisons test (nonparametric). We did not observe any statistically significant changes in clinical and biochemical salivary parameters between the two preemptive protocols in any period evaluated. We conclude that patients can be submitted to both preemptive protocols without significant differences in clinical and biochemical salivary parameters. significant differences in clinical and biochemical salivary parameters.

A terapia preemptiva melhora a qualidade de vida do paciente após remoção dos terceiros molares, contudo não há um consenso sobre o protocolo preemptivo mais eficiente. O objetivo foi comparar dois protocolos preemptivos da dexametasona (DEXA) com relação aos parâmetros clínicos (edema, trismo e dor), fluxo salivar (FS) e parâmetros bioquímicos salivares: pH, capacidade tamponante (CT), proteína total (PT), fosfatase alcalina total (FAL), fosfatase ácida total (FAT), lactato desidrogenase (LDH), cálcio (Ca) e Fósforo (P). Este estudo clínico randomizado, duplo-cego e boca- dividida, foi realizado com oito mulheres, com média de idade 20,89 anos, sem problemas de saúde local e sistêmica, que necessitaram de extrações bilaterais dos terceiros molares superiores e inferiores. Cada uma das pacientes teve remoções cirúrgicas bilaterais em duas sessões, com um intervalo de 20 dias entre as sessões. Em cada procedimento foi empregado aleatoriamente um protocolo preemptivo: DEXA pré-operatória via oral na dose usual, 8 mg, 1 hora antes da cirurgia (grupo controle) e a dose usual fracionada, 4 mg, 8 e 1 hora antes da cirurgia (grupo experimental). Todas as voluntárias assinaram o termo de consentimento livre e esclarecido (CAAE44625815.8.0000.5420). Os parâmetros clínicos foram mensurados no pré-operatório imediato e no pós-operatórios de 2 e 7 dias. Nos mesmos períodos, amostras de saliva total não-estimulada foram coletadas pelo método de expectoração entre 14h00- 16h00. Após o processamento, as alíquotas do sobrenadante foram armazenadas à - 80 °C até suas análises por métodos espectrofotométricos. Os protocolos preemptivos foram comparados entre si utilizando-se o teste t de Student (p < 0,05). Para comparar os resultados antes da cirurgia e no pós-operatório de cada protocolo preemptivo foi utilizado a análise estatística ANOVA, seguida pelo teste de Tukey (dados paramétricos) e o teste de Kruskal Wallis seguido do teste post hoc de comparações múltiplas de Dunn (não-paramétricos). Não observamos alterações estatisticamente significantes dos parâmetros clínicos e bioquímicos salivares entre os dois protocolos preemptivos no período avaliado. Concluímos que as pacientes podem ser submetidas a ambos os protocolos preemptivos sem diferenças significantes nos parâmetros clínicos e bioquímicos salivares.
Salivary clinical and biochemical parameters after two preemptive protocols of dexamethasone in the removal of third molars in women
Keywords: Dexamethasone; Cirurgia bucal; Dexametasona; Saliva; Enzinas